Configuração institucional da Secretaria da Controladoria Geral do Estado de Pernambuco : uma perspectiva institucional e apreciativa - SOUTO, Saulo Diógenes Azevedo Santos (2017)
This dissertation aims to analyze how the Secretary of the Comptroller Geral of the State of Pernambuco (SCGE/PE) can be institutionally configured, according to the institutional and appreciative perspectives, as a positive organization. Five interdisciplinary themes were used: control in the public sector, internal control, control, institutional theory and appreciative theory, which grounded the discussion concerning both the institutionalization process and the identification of factors indicative of SCGE/PE as an organization positive, in a context of accountability. To do so, a combination of the 5-D model (D1 Definition, D2 Discovery, D3 Dream, D4 Design and D5 Destiny was elaborated, at the center of which is the affirmative topic of the research, along with the analytical elements of the process of institutionalization and the positive and generative logic. In addition to documentary survey, appreciative interviews, traditional interviews and workshops were used. A collaborative group was formed, composed of six members of SCGE/PE (representatives of the strategic, managerial and operational levels) and two of its former leaders, who a played role in the process of collecting and analyzing data, as agents from the various professional areas and varied expertise in the organization. In the descriptive-interpretative process employed, data collection and analysis were integrated and validated, along with the collaborative group. Thus, the work traces the continuum of the institutional configuration attributed to SCGE/PE, closely associated with the construction of capacities linked to the historicity of organizational life, together with the appreciation of the positive nucleus identified in each "D" investigated, from which emerges the typification of an accountability institution. The results indicate that, in the SCGE/PE coexist patterns of habitualization/objectification of the organizational structure and governance model adopted, which are aligned with the four macrofunctions of internal control (Ombudsman, Government Audit, Controlling and Inspector General’s Office). This also explains its relevant position in strategic decisions within the state government, although it is still necessary to broaden its institutional recognition in front of society. In an accountability context, attention is also drawn to the development of expansive, generative and collaborative competences in SCGE/PE, as found in positive organizations. Finally, the conclusion is that SCGE/PE can be understood as representative of an internal control paradigm that is distanced from not only a form of repressive action to corruption but also more in line with preventive and guiding practices in decision making by the public manager. Thus, this places it at the center of the debate of the current Brazilian institutional context.